Physico-chemical properties and antibacterial drug performance of amoxicillin from streets in Bamenda, Cameroon - Teke, Gerald N.; Junior, Christian V.; Tamekou, Stephen L.; Nkengla, Penn-Edelqueen W.; Kuiate, Jules R. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The advent of microbial drug resistance creates a concern about the quality of anti-infective drugs. The rise in some microbial resistance to therapy has urged us to investigate physico-chemical properties and antibacterial performance of amoxicillin from streets in Bamenda, Cameroon. Methods: Amoxicillin samples were purchased from street vendors in Bamenda. Cameroon. Visual inspection was done for defects and signs of discoloration, deterioration or other physical disfiguration. Weight uniformity test for each sample of antibiotic tablet was carried out. The time for drug disintegration for each sample of amoxicillin was evaluated. Microbial antibiotic susceptibility tests were done using both the agar disc diffusion and micro well broth dilution methods to check drug performance. Data analysis was done and comparison checked with Student-Newman-Keuls at p<0.05. Results: The mean weight of amoxicillin drugs ranged from 632.00±11.5 to 748.06±17.9 mg. Tablets from Austria had a significant decrease in weight compared to those from Germany and Nigeria. This was similar with the capsules from India and China. Average disintegration varied significantly from as small as 2.2 to 14.4 minutes. All the amoxicillin samples were active against the tested bacteria with mean zones of inhibitions ranging from 8.33±0.57 to 39.33±0.57 mm. The MICs and MBCs values range from 1 to 64 µg/ml. For the same bacterium the growth inhibitory effects of the various drugs were not all similar. Conclusions: Some of the amoxicillin samples studied in this paper showed significant differences in their weights and performances (antibacterial activities). Probably the required amount of API was not respected.